PEMASANGAN PHOTOCELL PADA LAMPU PJU SEBAGAI UPAYA PENINGKATAN EFEKTIFITAS PENERANGAN DI LORONG TGK.MUHAMMAD DESA PAYA BUJOK SEULEUMAK LANGSA ACEH - Fahril, M. Ari; Naziah, Afrahun; Siregar, Ginda Maruli Andi; Musfirah, Rizka (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
The public street lighting (PJU) in Lorong Tgk. Muhammad consists of 2 units. So far, the installed street lights have been operated manually using a miniature circuit breaker (MCB). This pattern is certainly not effective and efficient because it requires residents living around the street lights to take the time to turn them on and off. Therefore, this service will focus on modifying street lights with photocell technology. The result of the activity is the installation of photocell technology at 2 points of street lights, along with an increase in knowledge and skills of residents related to photocell technology.